Electron-beam-induced deposition in ultrahigh vacuum: Lithographic fabrication of clean iron nanostructures - Lukasczyk, Thomas; Schirmer, Michael; Steinrück, Hans-Peter; Marbach, Hubertus (Small, 2008)
The generation of nanostructures with arbitrary shapes and well-defined chemical composition is still a challenge and targets the core of the fast-growing field of nanotechnology. One approach is the maskless nanofabrication technique of electron-beam-induced deposition (EBID). Up to now, the purity of these EBID structures has been rather poor. Here we demonstrate that by performing the EBID process solely under ultrahigh vacuum conditions, the lithographic generation of iron nanostructures on Si(100) with an unprecedented purity of higher than 95% is possible. One particular new aspect is the formation of EBID deposits with reduced size in a strain-induced diffusive process, resulting in deposits significantly smaller than 10 nm. © 2008 Wiley-VCH Verlag GmbH & Co.